THE INFLUENCE OF MOTIVATION AND WORK DISCIPLINE ON PERFORMANCE OF STATE ELEMENTARY SCHOOL TEACHERS AT BATU AJI - Beela Safira Indriningsih; Wasiman Wasiman (SEAN Institute, 2023)
Employees play an important role for every company where employees are used as a system that drives all parts so that they are neatly arranged and in accordance with the expectations of the company owner. Employee performance has several factors that can influence it, including motivation and work discipline. This study aims to analyze the effect of motivation and work discipline on the performance of public elementary school teachers in Batu Aji. The design of this study uses research design and quantitative research methods. The data collection technique was by distributing questionnaires to 150 respondents, namely public elementary school teachers in the Batu Aji sub-district. The results of this study indicate that motivation and work discipline partially and simultaneously have a significant effect on teacher performance. The results of the test for the coefficient of determination show that motivation and work discipline partially and simultaneously have a significant effect on teacher performance by 55 percent, while the rest are influenced by other variables not examined in this study.